Efektivitas Blended Laboratory terhadap Kualitas Laporan Praktikum Fisika Siswa - Agung Sugiarto; Hamdi Akhsan; Sardianto Markos Siahaan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze differences in the quality of physics practicum reports produced by 8th-grade junior high school students across three learning models: virtual experiments (PhET), real experiments, and blended laboratory. The study employed a quantitative approach using a quasi-experimental, non-equivalent control group design. The participants consisted of 45 students divided into three groups. The assessment instrument was a practicum report rubric covering objectives, procedures, data analysis, result interpretation, and evidence-based conclusions. Data were analyzed using One-Way ANOVA after satisfying the assumptions of normality and homogeneity. The results revealed significant differences among the groups (F(2,42) = 135.813; p < 0.001) with a very large effect size (η² = 0.866). The blended laboratory group achieved the highest scores compared to the other groups. Keywords: Blended Laboratory, Scientific Communication, Report Quality, PhET Simulation, Physics Practicum